FORMULA STRUKTUR NOVEL POPULER INDONESIA PERIODE 1970-1980 - Redyanto Noor; Sukarjo Waluyo; Ary Setyadi (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2022)
Since the growth of the Indonesian press industry in the 1970s, popular novels have been carried away by the rapid development of the mass media world. Because, there are facts and data that most of Indonesia's popular novels were originally published as serials in newspapers and magazines. Conclusively, people can classify certain novels into